Teknologi Informasi dan Komunikasi (TIK) Sebagai Sumber Belajar Kreatif dan Inovatif dalam Pembelajaran PAI Islam di Ruang Lingkup Madrasah - Suhirman Suhirman; yola Novriyana; Rafika Dewi Septia; Yenni Pusvita Dewi (Al-Bahtsu: Jurnal Penelitian Pendidikan Islam, 2024)
This study aims to analyze ICT as a creative and innovative learning resource in Islamic Religious Education learning in the Madrasah scope. This study uses a literature approach (library). Research Results: Aspects that influence ICT learning resources in Islamic Religious Education learning are Messages, Humans, Techniques, Materials, and Tools/Equipment. The benefits of ICT learning media are that it can make it easier for teachers to deliver material and make learning more interesting so that it gets students' attention and increases their learning motivation. Creative and innovative ICT media sources in Islamic Religious Education learning are: (1) Communication technology (email, google, instagram, facebook, twitter, weverse, tiktok and other media). (2) Computer Technology (Computer/Laptop). (3) Computer network technology (internet, wifi, LAN, and others). (4) Multimedia technology (CD player, speaker). In addition, teachers can utilize ICT in the form of e-books, journals, or E-Libraries (digital libraries), social media to obtain materials and share knowledge.